The Effectiveness of Online Teaching and Learning in Polman Bandung - I Gusti Bagus Rai Utama (Soshum: Jurnal Sosial dan Humaniora, 2021)
This research was conducted accidentally which included 109 respondents. Data collection was carried out by survey using an online question instrument (google form) distributed on various social media. The level of effectiveness in the form of social distancing to address the development of information related to COVID-19 is effective in reducing the rampant transmission of COVID-19 through human relations by humans by 82%. The relationship between the respondent's work and the impact of the pandemic COVID-19 on the work of the respondent statistically using the Chi-Square Test were not significant. The relationship between the respondent's work and the impact of the pandemic COVID-19 on work from home has been shown to have a significant effect. The relationship between respondents’ work and the impact of the pandemic COVID-19 on out-of-town travel had no significant effect. Relationship between respondents' work and the impact of the pandemic COVID-19 on meetings and meetings did not have a significant effect the relationship between Respondent's Work and the Impact of the pandemic COVID-19 on work activities proved to have a significant effect. The relationship between respondents’ work and the impact of the pandemic COVID-19 on meetings with consumers had no significant effect.